“FOR THE HAPPINESS OF THE PEOPLE WHO INHABIT THIS CLIMATE”: MANOEL ANTÔNIO CORIOLANO AND THE WRITING OF HISTORICAL NEWS OF THE PROVINCE OF RIO GRANDE DO NORTE (1875-1881) (Muitas Vozes, 2022)
In this article I have as scope the writing of the history of Manoel Antônio de Oliveira Coriolano (1835-1922) about the province of Rio Grande do Norte in the late 70s of the 19th century. Coriolano was one of the pioneers in historiographical work in Rio Grande do Norte. His historiographical writing was anchored in the chorographic model and was concerned with recording the history of the village of Apodi, through the recovery of documents from the city council, the registry office and his own records concerning rainfall. Furthermore, in this writing of the present time, by revealing the situation of the province of Rio Grande do Norte, the thinker of history triggered a narrative that would become modular for writers of subsequent periods, with the construction of space under the sign of the problem of drought. , in which hunger was evoked as a central character in the story. In this sense, the writing of Manoel Coriolano's history can be understood as an exercise that shaped the initial process of invention of historiographical traditions in Rio Grande do Norte.